2013
DOI: 10.1007/s13187-013-0576-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Breast Cancer Prevention Information-Seeking Among Rural Women: Will Provider Mobile Messages Work?

Abstract: Although growing research supports cancer survivor information-seeking, little is known about breast cancer prevention information-seeking among women. The purpose of the study was to examine differences in breast cancer risk factor knowledge, information sources, and desired mobile messages among Hispanic and non-Hispanic rural women. Women were recruited to complete a survey at an imaging center during a mammography screening visit. A total of 156 women (mean age = 61, SD = 12.07) completed the survey. Breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…7 In New Mexico in the United States, a study on cancer prevention knowledge, health seeking behavior, and desire for mobile messaging among Hispanic and non-Hispanic rural women concluded that mobile technology may fill an important gap in educational needs on cancer prevention. 8 A study in Botswana showed improved access to see-and-treat cervical cancer screening via mobile telemedicine for women in remote regions. 9 Another pilot program in Botswana using telemedicine to reach regions with few medical specialists demonstrated the need for both strong management and local partnerships to achieve sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…7 In New Mexico in the United States, a study on cancer prevention knowledge, health seeking behavior, and desire for mobile messaging among Hispanic and non-Hispanic rural women concluded that mobile technology may fill an important gap in educational needs on cancer prevention. 8 A study in Botswana showed improved access to see-and-treat cervical cancer screening via mobile telemedicine for women in remote regions. 9 Another pilot program in Botswana using telemedicine to reach regions with few medical specialists demonstrated the need for both strong management and local partnerships to achieve sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the study conducted on 156 women living in rural areas (divided into two groups -Spanish women and women of different origin) suggest that doctors and other health education specialists should use mobile devices (applications) in order to promote the knowledge concerning breast cancer prophylaxis. 28 Another form of awareness raising, which has been used for years, are events held with the aim to show the possibility of taking part in prophylactic examinations and contact with experts (e.g. a dietician, diabetes experts, dermatologist).…”
Section: Discussionmentioning
confidence: 99%
“…Television, radio and new technological developments such as the internet affect women's health beliefs with regard to the early diagnosis of breast cancer in a positive way, and increase their motivation (Kim et al, 2001;Yi et al, 2008;Heo et al, 2013;Kratzke and Wilson, 2013).…”
Section: Effectiveness Of Online Education In Teaching Breastmentioning
confidence: 99%